(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
In the present paper, energetic properties of wood chips of the species Robinia pseudoacacia (clones Ambigua, Debrecenyi 2, Göri, Matyasi, Nyirsegi, Rozaszin, Zalyi) ere determined, relative humidity of chips during a harvest, bulk density, namely the share of bark in chips, chemical composition of combustibles of chips, ash content in dry mass of biofuel, and lower heating value. Green wood chips made of dendromass from plantations consist of juvenile wood and juvenile bark. The share of juvenile bark in green wood chips of the analyzed clones of Robinia pseudoacacia is XB = 22.97 ± 1.95 %. The nitrogen content in green wood chips made of Robinia pseudoacacia trees grown on plantation is 8 times higher than the nitrogen content in the combustibles of fuelwood of broadleaved tree species, which has negative impact on the production of emissions – concentration of nitrogen oxides NOx in combustion products. The share of inorganic substances determined by the form of ash content Ad = 1.73 % puts the analyzed biofuel into the category of low-ash fuels. The lower heating value of green wood chips of the individual Robinia pseudoacacia clones analyzed in dry state is Qn = 18.0 MJ.kg-1.